Factors influencing the awareness of having life insurance among Generation Y employees in Selangor / Nurul Aina Noor Aidee - Noor Aidee, Nurul Aina (Faculty of Business and Management, 2019)
The present study seeks to examine the factors influencing the awareness of having life insurance among Generation Y employees in Selangor. The independent variables consist of four factors including income, knowledge level, perception and promotion. While the dependent variable is the awareness of having life insurance. A total of 192 questionnaires was keyed in and analysed by using SPSS software version 20. Furthermore, this research has used non-probability, convenience sampling to obtain accurate data from the targeted respondents. All data were collected for the purpose to create analysis of descriptive, correlation and regression analysis. In this study, findings show that there were three independent variables that has a significant relationships towards the awareness of having life insurance which are income, knowledge level, perception and promotion. From this we can see that the finding is useful for the insurance industry and organizations on the importance of life insurance so that they can amend better insurance policies and increase the number of insured with an adequate coverage.